Legal Protection for Doctor who Performs Medical Treatments that Lead Patient to Death - Filosophia Putri Kemala Dewi (Rechtsidee, 2019)
This research was carried out due to frequent accusations that doctors performed malpractice. Accusations of errors in medical treatment are often found in the field. The objectives of this research are to: 1) examine and analyze forms of legal protection for doctors/ dentists in providing medical services who carry out independent practices as well as those working in hospitals, 2) review and analyze legal liabilities of doctors/ dentists in carrying out medical profession that leads patients to death. This research applies statute and conceptual approaches that is equipped with a case approach. The analysis results of the research indicated that the State provides legal protection for a doctor/ dentist through Article 27 paragraph (1) of Law No. 36 of 2009 concerning Health, Article 50 point (a) Law No. 29 of 2004 concerning Medical Practice, Article 24 paragraph (1) Government Regulation No.32 of 1996 concerning Health Workers, and Article 57 points (a) Law No. 36 of 2014 concerning Health Workers. Moreover, besides the above positive laws, legal protection for doctors/ dentists who work in hospitals also applies Article 46 of Law No. 44 2009 about hospitals and respondeat superior doctrine.